The risk of serious bacterial infections among young ex-premature infants with fever - Barak-Corren, Yuval; Elizur, Yoav; Yuval, Shira; Burstyn, Amalia; Deri, Noy; Schwartz, Shepard; Megged, Orli; Toker, Ori (Frontiers in Pediatrics, 2022)
Background and Objectives: To determine the rate of serious-bacterial-infections (SBI) in young ex-premature infants with fever, and to develop a risk-stratification algorithm for these patients. Methods: A retrospective cohort study including all infants who presented to the pediatric emergency department (ED) of a tertiary-care university-hospital between 2010 and 2020 with fever (≥38°C), were born prematurely (<37-weeks), had post-conception age of <52-weeks, and had available blood, urine, or CSF cultures. The rates of SBI by age-of-birth and age-at-visit were calculated and compared to a cohort of matched full-term controls. Results: The study included a total of 290 ex-premature cases and 290 full-term controls. There were 11 cases (3.8%) with an invasive bacterial infection (IBI) of either bacteremia, meningitis or both and only six controls (2.1%) with IBI (p=0.32). Over 28-days chronologic-age, there were 10 (3.6%) IBIs among cases and no IBIs among the controls (p=0.02). There were eight (3%) cases and three (1%) controls with IBI who were well-appearing on physical examination (p=0.19). All eight well-appearing ex-premature infants were under 60-days adjusted-age, seven of whom (88%) were also under 28-days adjusted-age. There were 28 (10.6%) cases and 34 (12%) controls with urinary tract infection (UTI) (p=0.5). Among cases under 60-days adjusted-age, urinalysis was not reliable to exclude UTI (50% negative). Conclusions: Well-appearing ex-preterm infants have a significant risk for IBI until the adjusted age of 28-days and for UTI until the adjusted age of 60-days. Further studies are needed to evaluate the approach to fever in this unique population.